The diagnostic impact of transesophageal echocardiography in a patient after post-cardiac arrest syndrome - GÜL, FETHİ (My University, 2023)
Introduction: The impairment of coagulation and fibrinolysis processes may be observed after cardiac arrest. Echocardiography is important for determining the causes of the cardiac origin of pulmonary embolism, and, simultaneously, mobile thrombi can be rarely visualized in the ventricule. In this report, we present a case of the intraventricular mobil thrombus that we detected with trans-esophageal echocardiography (TEE) in a patient who underwent CPR for 35 minutes after out of hospital cardiac arrest. Case: A 54-year-old male patient with coronary artery disease (CAD) and 2-vessel stents was admitted to the emergency service after cardiac arrest. He was admitted to the intensive care unit (ICU) and targeted temperature management could not be applied since it was too late. Brain MRI revealed hypoxic ischemic encephalopathy. Due to recurrent Grampositive infections despite appropriate antibiotic treatment, in addition to other screening tests, a bedside TEE performed by an intensivist revealed a 27x23 mm mobile thrombus in the left ventricle (Figure 1). Surgical intervention methods were not considered by cardiovascular surgens, then antithrombotic treatment was administered. After the achievement of infection control with effective antibiotherapy, the patient was discharged to the palliative center on the 99th day of hospitalization with the tracheostomy and percutaneous endoscopic gastrostomy Discussion: It is crucial that elucidation of the culprit of the recurrent infections in intensive care patients and focal control should be ensured as soon as possible. In our patient, we investigate the presence of vegetation in heart with the TEE following recurrent Gram-positive cocci growth in blood cultures. Guidelines recommend TEE as the first test for suspected infective endocarditis, usually combined with TTE, so we think that intensivists should use it more widely in intensive care practice.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; Transesophageal echocardiography; cardiac arrest; mobile thrombus